2012
DOI: 10.1103/physrevd.86.014507
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries of hadrons after unbreaking the chiral symmetry

Abstract: We study hadron correlators upon artificial restoration of the spontaneously broken chiral symmetry. In a dynamical lattice simulation we remove the lowest lying eigenmodes of the Dirac operator from the valence quark propagators and study evolution of the hadron masses obtained. All mesons and baryons in our study, except for a pion, survive unbreaking the chiral symmetry and their exponential decay signals become essentially better. From the analysis of the observed spectroscopic patterns we conclude that co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 62 publications
7
78
0
Order By: Relevance
“…This confirms the mechanism through which chiral symmetry is realized in the parity doublet model. Rather than yielding vanishing masses in the chiral limit the baryon masses become degenerate at m ± = m 0 , as observed in the lattice QCD simulations upon chiral symmetry restoration [17][18][19].…”
Section: A Extended Mean-fieldmentioning
confidence: 77%
“…This confirms the mechanism through which chiral symmetry is realized in the parity doublet model. Rather than yielding vanishing masses in the chiral limit the baryon masses become degenerate at m ± = m 0 , as observed in the lattice QCD simulations upon chiral symmetry restoration [17][18][19].…”
Section: A Extended Mean-fieldmentioning
confidence: 77%
“…It is possible that exotic hadron states can explain the discrepancy between the lattice results and hadron resonance gas model for T > 140 MeV. Another possibility could be the partial restoration of the chiral symmetry and the corresponding change in the static-light hadron masses, as indicated in a recent lattice study [41].…”
Section: Comparison With Lattice Resultsmentioning
confidence: 99%
“…It was found that this dependence significantly deviates from the expectation M ∝ N 0 c and Γ ∝ 1/N c for pure qq structure [24]. The chiral properties and issues related to chiral restoration were considered for example in [25,26].…”
Section: Jhep04(2014)162mentioning
confidence: 99%